2019
DOI: 10.3389/fpls.2019.00899
|View full text |Cite
|
Sign up to set email alerts
|

ABCG36/PEN3/PDR8 Is an Exporter of the Auxin Precursor, Indole-3-Butyric Acid, and Involved in Auxin-Controlled Development

Abstract: The PDR-type ABCG transporter, ABCG36/PDR8/PEN3, is thought to be implicated in the export of a few structurally unrelated substrates, including the auxin precursor, indole-3-butyric acid (IBA), although a clear-cut proof of transport is lacking. An outward facing, lateral root (LR) location for ABCG36 fuelled speculations that it might secrete IBA into the rhizosphere. Here, we provide strong evidence that ABCG36 catalyzes the export of IBA – but not of indole-3-acetic acid – through the plasma membrane. ABCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…IBA is transported over long distances by several carriers, including ABCG36/PEN3/PDR8 [ 42 ] and ABCG37/PDR9/PIS1 [ 42 44 ], both of which mediate IBA efflux through the plasma membrane (reviewed in [ 48 , 49 ]). These IBA transporters play important regulatory roles in cellular IBA levels (reviewed in [ 50 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IBA is transported over long distances by several carriers, including ABCG36/PEN3/PDR8 [ 42 ] and ABCG37/PDR9/PIS1 [ 42 44 ], both of which mediate IBA efflux through the plasma membrane (reviewed in [ 48 , 49 ]). These IBA transporters play important regulatory roles in cellular IBA levels (reviewed in [ 50 ]).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been reported that the ibr1 , 3 , 10 mutant displays small cotyledons [ 34 ]. More interestingly, mutants with defects in the IBA efflux carriers PENETRATION3 (PEN3; [ 42 ]) and PLEIOTROPIC DRUG RESISTANCE 9 (PDR9; [ 42 44 ]) have larger cotyledons, when compared to the WT, possibly due to high intracellular IBA, and thus higher endogenous IAA levels in these organs [ 42 ]. From these findings, IBA-derived IAA plays an important role not only in roots but also in plant shoots and particularly in cotyledons during their early developmental stage.…”
Section: Introductionmentioning
confidence: 99%
“…However, their folds in a family are highly conserved, thus homology modeling can provide high-quality models [34][35][36][37]. We chose AtABCG36/PEN3/PDR8 [38] from the model plant Arabidopsis thaliana, which is a well-investigated full transporter of the ABCG subclass for that no structures yet exist. When the homology model exhibiting two ABCG2-like TMDs (Fig.…”
Section: Af2 Can Provide Hints For Investigating Abc Structure-associ...mentioning
confidence: 99%
“…We included also ABCG37/PDR7/PIS1, shown to act redundantly with ABCG36 in IBA transport, and ABCG35, the closest homolog of ABCG36 (81.1% sequence identity), and both were also negative. We tested the same set also for IBA transport and discovered that all tested ABCGs were capable of exporting IBA, although ABCG34, G35 and G40 to a lesser amount than ABCG36 and G37 (Aryal et al, 2019;Ruzicka et al, 2010;Fig. 1B).…”
Section: Abcg36 Is An Exporter Of Camalexin That Functionally Interac...mentioning
confidence: 96%